SEASONAL PATTERN OF WIND INDUCED UPWELLING OVER JAVA-BALI SEA WATERS AND SURROUNDING AREA - - Siswanto; - Suratno (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2008)
The influence of monsoonal wind to coastal upwelling mechanism which is generated by Ekman transport was studied here by analyzing wind stress curl (WSC) distribution over Java-Bali Sea waters and its surrounding area. Surface wind data were used as input data to calculate curl of wind stress in barotropic model. Confirmation with Corioli effect in the Southern Hemisphere, it could be known that negative curl value has relation with vertical motion of sea water as resulted by Ekman transport. Result of analysis showed that negative curl near coast over Java Sea which is stretching to Lombok Sea occurred in December to April when westerly wind of the North West Monsoon actives. It can be guidance and related with season of coastal upwelling in the region. Reversal condition, the occurrance of coastal upwelling in the south coast of JAva island related with the negative value of WSC that occurs since easterlies wind take place in May to August as a part of South East Monsoon episode. Generally, upwelling occurrance in the field of study is a response to the Monsoon circulation. This study with related data such as sea surface temperature, chlorophyll concetration and mixed layer depth that derived from satellite imaging data National Oceanic and Atmospheric Administration Advanced Very High Resolution Radiometer (NOAA-AVHRR), Aqua/Modis and sea viewing Wide Field-of-view Sensor(Sea WiFS) shows as magnificent confirmation pattern. So applying WSC to recoqnize upwelling zone is alternatively way as climatic approach to maps potential fertilizing of sea water in maritime-continent Indonesia. Key words: coastal upwelling, Ekman transport, Java-Bali Sea, Monsoon circulation, upwelling.